O engajamento ocupacional materno em unidade canguru diante do contexto de pandemia por covid-19 - Benassule, Stéfannie Cardoso (2023)
Background: Worldwide rates of prematurity and low birth weight range from 15 to 20%, these being risk factors for neonatal mortality. Still, the complications of premature birth are the main causes of death in the first five years of life. The Kangaroo Mother Care is a public policy that presents itself as an alternative to conventional neonatal care, aiming at the quality of care offered to low birth weight babies and their families. In the context of the COVID-19 pandemic, which required a sudden reorganization of hospital routines, there was an impact on the care guidelines recommended by the Method. In Brazil, the UCINCa were adapted in their work flows, with the adoption of care such as the prevention of crowds and access only to asymptomatic people. Considering that the Kangaroo Mother Care is a model of care that prioritizes the mother's participation in the care given to the child and that their engagement in the care of the baby is considered fundamental so that they can recognize themselves in motherhood, performing it is part of the maternal role, that begins in this period in which the newborn is in neonatal care. Objective: To understand the occupational engagement of mothers inserted in phase II of the Kangaroo Method in the face of the COVID-19 pandemic; specifically, to characterize the Kangaroo Intermediate Care Unit in the context of the COVID-19 pandemic and to identify aspects that favor and limit maternal occupational engagement in baby care. Method: Qualitative, descriptive and exploratory study. Data were collected during the baby's hospitalization, at the Kangaroo Intermediate Care Unit, in a reference Santa Casa de Misericórdia in the State of Pará. The following instruments were used for data collection: Sociodemographic Questionnaire; Semi-structured interview script; Occupational self-assessment – OSA-BR; and Field Diary. Data were systematized, tabulated and described in detail. The results of the interviews were analyzed based on content analysis, in the thematic modality. Results: Nine mothers of preterm newborns inserted in the second stage of the Kangaroo Method in the Intermediate Care Unit participated. From the data produced from the interviews, three thematic categories emerged: Daily routines in a kangaroo unit – taking care of the baby and taking care of yourself; Kangaroo position: Practicing and knowing the benefits and Performing the Kangaroo Mother Care during the COVID-19 pandemic, which unfold into nine subcategories that reveal aspects of the participants' engagement in the face of a new role played in the care of their premature baby and in a pandemic context . The results of the OSA-BR demonstrate the occupational competence related, mainly, to the care of the other and the reduction of the importance of the mothers in relation to their self-care in this context. Discussion: It is observed that understanding the Kangaroo Method from the occupational concept can favor the engagement of the participants, as it is about making the execution of care meaningful, seeking to relate the process of the mother-baby bond, learning according to the recommendations of the Method and with the support of the health team, as well as the difficulties and feelings that permeate this moment. Conclusion: The research brings elements for further investigations on the subject in the perspective of understanding the Kangaroo Mother Care as an occupation for the care of the baby, therefore, loaded with meanings for the mother, in which they can experience the occupational engagement during the implementation of the Method, consolidating and expanding the role of occupational therapists in kangaroo neonatal units.